Oral hyaluronic acid in patients with knee osteoarthritis - Andor, Bogdan Corneliu; Cerbu, Simona (Progress in Nutrition, 2019)
The international guidelines agree that management of knee osteoarthritis (OA) requires both non-pharmacological, and pharmacological approaches and suggest initiating a background therapy with chronic symptomatic slow-acting drugs for osteoarthritis (SYSADOAs), such as hyaluronic acid (HA). Oral HA treatment is now widely used because of its safety, good results in daily clinical practice, and relative low cost for knee pain. On the other hand, oral HA has been the source of much research in the last years. Several trials have evidenced the good efficacy of oral HA in reducing pain and improving joint functionality in mild to moderate knee osteoarthritis, but critical issues concerning the parameters used in these studies to measure the end points still persist. In few cases objective parameters (i.e. ultrasound) have been considered and no study correlated them with specific scales like visual analogue score (VAS) and Knee injury and Osteoarthritis Outcome Score (KOOS) to improve patient assessment. This could be the goal of future researches.